2010
DOI: 10.3151/jact.8.35
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Textile Reinforced Concrete (TRC) / Concrete Composite Elements

Abstract: In this paper the response of composite structural elements cast against thin-walled stay-in-place (SiP) formwork elements made of Textile Reinforced Concrete (TRC) is experimentally investigated and analytically approached. TRC comprises an innovative composite material consisting of fabric meshes made of long fibre yarns (e.g carbon, glass, aramid or basalt) arranged in at least two (typically orthogonal) directions and embedded in a cementitious fine-grained matrix. Two types of reinforced concrete specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 4 publications
2
14
0
1
Order By: Relevance
“…After hardening of the concrete, the stay-in-place formwork gets an additional structural function and acts as a (partial) tensile reinforcement of the final concrete structure. The structural capacity of stay-in-place formwork in textile reinforced concrete (TRC) was already demonstrated for beam elements in Brameshuber et al (2004), Papantoniou and Papanicolaou (2008), Papanicolaou and Papantoniou (2010) and at our university for the used composite GFTR-IPC in Verbruggen et al (2013) and De Sutter et al (2014). Both materials show similar results as stay-in-place formwork because the material properties are also very similar.…”
Section: Introductionsupporting
confidence: 58%
“…After hardening of the concrete, the stay-in-place formwork gets an additional structural function and acts as a (partial) tensile reinforcement of the final concrete structure. The structural capacity of stay-in-place formwork in textile reinforced concrete (TRC) was already demonstrated for beam elements in Brameshuber et al (2004), Papantoniou and Papanicolaou (2008), Papanicolaou and Papantoniou (2010) and at our university for the used composite GFTR-IPC in Verbruggen et al (2013) and De Sutter et al (2014). Both materials show similar results as stay-in-place formwork because the material properties are also very similar.…”
Section: Introductionsupporting
confidence: 58%
“…In the case of strengthening of RC structures using TRC significant improvement in ultimate load capacity of existing structures can be achieved, while its application is simple and can be applied in any complex shape [21][22][23]. The addition of short fibers in the matrix of TRC is also studied by several researchers and found that the hybridization of short polymeric fibers with textile have positive effects on various properties of TRC-e.g., increase in ultimate tensile strength of TRC, reducing the crack width in TRC, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the past studies, the development of stay-in-place formwork using TRC has been conducted around horizontal members such as slabs and beams [4,5,6,7]. Recently, experimental works on the performance of TRC stay-in-place formwork applied for a vertical member such as columns [8,9] and an asymmetric shell structure [10] have also been performed. Existing studies have demonstrated that the structural performance of a column using TRC is superior to that of a conventional RC column through the experimental test of specimens.…”
Section: Concept Of Stay-in-place Formwork and Textile Reinforced Conmentioning
confidence: 99%